Occupational Safety in the Age of the Opioid Crisis: Needle Stick Injury among Baltimore Police - Cepeda, Javier A. (J Urban Health, 2017)
At a time of resurgence in injection drug use and injection-attributable infections, needle stick injury (NSI) risk and its correlates among police remain understudied. In the context of occupational safety training, a convenience sample of 771 Baltimore city police officers responded to a self-administered survey. Domains included NSI experience, protective behaviors, and attitudes towards syringe exchange programs. Sixty officers (8%) reported lifetime NSI. Officers identifying as Latino or other race were almost three times more likely (aOR 2.58, 95% CI 1.12–5.96) to have experienced NSI compared to whites, after adjusting for potential confounders. Findings highlight disparate burdens of NSIs among officers of color, elevating risk of hepatitis, HIV, and trauma. Training, equipment, and other measures to improve occupational safety are critical to attracting and safeguarding police, especially minority officers.